Mechanisms of cholesterol and saturated fatty acid lowering by Quillaja saponaria extract, studied by in vitro digestion model. Issue 4 (16th March 2015) - Vinarova, Liliya; Vinarov, Zahari; Damyanova, Borislava; Tcholakova, Slavka; Denkov, Nikolai; Stoyanov, Simeon
Abstract : High molecular weight polyphenols in Quillaja saponaria extract decrease the bioaccessibility of cholesterol during in vitro digestion, by inducing cholesterol precipitation. Abstract : Quillaja saponin extracts are known to reduce plasma cholesterol levels in humans. Here we study the mechanism of this effect with Quillaja Dry saponin extract (QD). In vitro model of triglyceride lipolysis is used to quantify the effect of QD on the solubilization of cholesterol and of the lipolysis products (fatty acids and monoglycerides) in the dietary mixed micelles (DMM). We found that QD extract decreases significantly both the cholesterol (from 80% to 20%) and saturated fatty acids (SFA, from 70% to 10%) solubilised in DMM. Series of dedicated experiments prove that QD may act by two mechanisms: (1) direct precipitation of cholesterol and (2) displacement of cholesterol from the DMM. Both mechanisms lead to increased cholesterol precipitation and, thus, render cholesterol bio-inaccessible. We prove also that the saponin molecules are not the active component of QD, because highly purified Quillaja extract with very similar saponin composition does not exhibit cholesterol-lowering or SFA-lowering effect. The effect of QD extract on cholesterol solubilisation is most probably caused by the high-molecular weight polyphenol molecules, present in this extract. The reduced SFA solubilisation is caused by Ca 2+ ions of relatively high concentration (1.25 wt%), also present in QD extract, which precipitate the fatty acids into calcium soaps.